Economic burden of opioid misuse focused on direct medical costs - Kim, Miryoung; Kim, Siin; Suh, Hae Sun (Frontiers in Pharmacology, 2022)
Background: Since their development, synthetic opioids have been used to control pain. With increased opioid use, problematic opioid prescription has also increased, resulting in a growing economic burden. However, there is a paucity of research studies on the economic burden of prescription opioid misuse in Asia, especially South Korea. Objectives: To estimate the incremental economic burden of prescription opioid misuse for the South Korean population. Methods: The National Health Insurance Service-National Sample Cohort database, covering 2% of the South Korean population between 2010 and 2015, was analyzed. Outpatients aged 18 or older who took one or more prescription opioids were selected. Based on their opioid prescription patterns, patients were classified into opioid misuse and non-misuse groups. The direct medical costs per person per year (PPPY) and the incremental economic burden of the opioid misuse group were explored using an exponential conditional model with a suitable distribution and log link function. All analyses were performed using SAS® Enterprise Guide version 9.4, and p < 0.05 was considered statistically significant. Results: The number of patients who had ≥1 opioid prescription was 345,020 including 84,648 (24.53%) in the opioid misuse group and 260,372 (75.47%) in the non-misuse group. The adjusted mean direct medical costs PPPY were estimated to be USD 401 for the opioid misuse group, which is 1.49 times significantly higher than that for the non-misuse group (p < 0.0001). The incremental economic burden of the opioid misuse group in the South Korean population was estimated to be approximately USD 0.52 billion for the period 2010–2015. Conclusion: Prescription opioid misuse was significantly associated with the increased economic burden. Along with proper policies for using opioids, it is necessary to monitor opioid prescription patterns to prevent opioid misuse and reduce the related economic burden.